An ultrastable large-area atomically flat 2D polymer dielectric for low-voltage flexible organic field-effect transistors. Issue 8 (14th February 2023) - Wang, Jiamin; Yuan, Jiangyan; Li, Bin; Wang, Zhaofeng; Ma, Chunli; Yang, Shuyuan; Yao, Jiarong; Ren, Yiwen; Wu, Xianshuo; Lei, Shengbin; Yang, Fangxu; Li, Rongjin; et al.
Abstract : Ultrastable centimeter-sized atomically flat 2D polymer thin films are produced by interfacial polymerization for flexible electronics. Abstract : 2D polymers (2DPs) are superb candidates as dielectric layers for flexible organic field-effect transistors (OFETs) because of their fascinating features including high stability, solution processibility, and inherent flexibility. However, the challenge to produce smooth and large-area 2DP thin films hinders the evaluation of their fundamental properties as a gate dielectric layer for flexible OFETs. Here, ultrastable centimeter-sized atomically flat 2DP thin films are produced by interfacial polymerization at the air–liquid interface. Solubility, spreading and reaction time are found to be key indispensable factors in determining the production of smooth and large-area 2DPs. Benefiting from their inherent properties, the 2DP thin films exhibit not only excellent insulating properties but also high solvent tolerance and high thermal stability, ensuring the construction of high-performance low-voltage flexible OFETs. These results shed light on a promising class of dielectric materials with both high quality and high stability for wearable electronics.